1998
DOI: 10.1136/gut.43.4.478
|View full text |Cite
|
Sign up to set email alerts
|

The influence of a preserved colon on the absorption of medium chain fat in patients with small bowel resection

Abstract: Background-Medium chain C8-C10 triglycerides (MCTs) improve fat absorption in short bowel patients. EVects on overall energy absorption remain unknown. Aims-To determine whether MCTs and medium chain fatty acids (MCFAs) are absorbed in the colon like the short chain fatty acids (SCFAs) or are lost in faeces similarly to long chain fatty acids (LCFAs). Methods-Nine small bowel resected patients without and 10 with a colon in continuity excreted 2-6 MJ/day and were randomised and crossed over between two high fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
90
2
3

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(98 citation statements)
references
References 24 publications
(14 reference statements)
3
90
2
3
Order By: Relevance
“…21,22 Diet and fecal nitrogen in grams were converted to diet and fecal grams of protein by multiplying by 6.25. The energy conversion factors were those of Atwater et al, as confirmed by Southgate and Durnin 23 : 17.6, 23.6, and 39.1 kJ/g for carbo-hydrate, protein, and fat, respectively.…”
Section: Balance Studiesmentioning
confidence: 99%
“…21,22 Diet and fecal nitrogen in grams were converted to diet and fecal grams of protein by multiplying by 6.25. The energy conversion factors were those of Atwater et al, as confirmed by Southgate and Durnin 23 : 17.6, 23.6, and 39.1 kJ/g for carbo-hydrate, protein, and fat, respectively.…”
Section: Balance Studiesmentioning
confidence: 99%
“…A peptide diet has a relatively high osmolality and thus can increase stomal output [151] . Little advantage comes from taking a diet of watersoluble medium chain triglycerides in place of normal fat [148] . The addition of glutamine (15 gm) to a litre of rehydration solution in patients with jejunostomy resulted in no additional benefit in terms of water or sodium absorption [152] .…”
Section: Undernutrition -Protein-energy Malnutritionmentioning
confidence: 99%
“…If a diet is high in monosaccharides D (-) lactic acidosis may occur (see below). Medium chain triglycerides are an alternative source of energy and are absorbed from the small and large bowel [145][146][147][148] . In order to increase the energy absorption, reduce the risk of renal stones and D (-) lactic acidosis, patients with a retained colon need a large totalenergy intake with a diet high in carbohydrate (polysaccharides) [29] , but not increased in fat (long chain triglycerides) and low in oxalate.…”
Section: Undernutrition -Protein-energy Malnutritionmentioning
confidence: 99%
See 1 more Smart Citation
“…The human colon has not often been considered to be a site of fat absorption; however, the small intestine absorbs only approximately 95% of dietary lipids after consumption of a typical Western diet. 149 Furthermore, some studies have suggested that colonic absorption of medium-chain fatty acids takes place in dogs, 150 rats, 151 and humans 152,153 and that glycerol accumulates in the colon when fat absorption is disturbed in the small intestine. 154 Accumulation of glycerol has been shown to alter the Lactobacillus and Enterococcus communities in the gut.…”
Section: Microbiota Interactionsmentioning
confidence: 99%